Improving Students’ Reading Comprehension And Building Self-Confidence Through Flip Learning (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
In this study, it is believed that students' reading comprehension abilities will improve as they learn English in the classroom and that it will encourage them to be enthusiastic in similar circumstances. To help students become more comfortable reading, better recognize what they read, and comprehend the meaning of the expressions they read, this research focuses primarily on improving students' reading comprehension in the form of congratulation text through flip learning. Flip learning presents a learning experience for students in the process of understanding, based on the average report in cycle I, the average score of students is 62.8 and in cycle II they were declared satisfied with the average category where students were able to achieve 87.8.